Ethnomedicinal plant use value in Lower Swat, Pakistan - Ali, Shujat; Sayed, Afzal Shah; Saeed, Rida Fatima; Iqbal, Javed; Ijaz, Shumaila; Munazir, Mehmooda (Ethnobotany Research and Applications, 2023)
Background: Plant-based traditional or folk medicines hold a great deal of promise as the foundation for medications for different diseases. Hence, the purpose of the present study is to document and preserve traditional knowledge among the people of Lower Swat. Methods: The field survey was conducted in 2018–2021, and 90 participants were interviewed using a semi-structured questionnaire. Information was collected predominantly from traditional practitioners, who are thought to have comparatively more knowledge and experience of using herbal medicine. During the discussions, notes were taken on the participants’ demographics, plant names, plant parts used, and methods of herbal preparation. The collected data were analyzed through statistical indices in Microsoft Excel (2016). Results: It was found that 118 species represented by 107 genera and 62 different families were used for various medicinal purposes. Our findings depicted that herbs (57.5%) were the most commonly used as compared to trees and shrubs, while leaves (37.06%) were commonly used plant part for therapeutic purposes. Lamiaceae (16 species) was the most important family, followed by Rosaceae and Asteraceae (7 species each). Among the modes of preparation, decoction, drying, heating, and infusion were the applied approaches. The data was also analyzed by using qualitative indices such as relative frequency of citation (RFC), use report (UR), fidelity level (FL) and use value (UV). The highest RFC (0.96) was recorded for Mentha spicata and Foeniculum vulgare while the highest FL for Berberis lycium (78%) and, Ajuga bracteosa (70%). The highest UR (4) was recorded for Ajuga parviflora, Pinus roxburghii and Pinus wallichiana. The highest UV (0.50) was recorded for Ziziphus oxyphylla. Conclusions: The results of the present study reflect that medicinal plants are the most important source of health care in lower Swat. But in the absence of understanding and intuitive collective approaches, mainly therapeutic plants are overexploited in the area. There is a dire need for awareness about sustainable use of medicinal plants and threatened species in particular. Keywords: Lower Swat, ethnobotany, medicinal plants, traditional knowledge, mode of preparation, aliments.